The Pipeline of Online Participation Inequalities: The Case of Wikipedia Editing. (28th February 2018) - Shaw, Aaron; Hargittai, Eszter
Abstract: Digital inequalities undermine the democratizing potential of the Internet. While many people engage in public discourse through participatory media, knowledge gaps limit engagement in the networked public sphere. Participatory web platforms have unique potential to facilitate a more equitable production of knowledge. This paper conceptualizes a pipeline of online participation and models the awareness and behaviors necessary to become a contributor to the networked public sphere. We test the theory with the case of Wikipedia editing, relying on survey data from a diverse, national sample of U.S. adults. Our findings underscore the multidimensionality of digital inequalities and suggest new pathways toward closing knowledge gaps by highlighting the importance of education and Internet skills for online stratification processes.